STRUCTURAL DYNAMIC DESIGN AND TEST VALIDATION OF VIBRATION TEST FIXTURES - SUN Ye; LU HaiTao; ZHANG HaiYing; FAN ZheLiang (Jixie qiangdu)
The structure of a complicated fixture is usually designed improperly using common methods,which are usually based on experience and formulas. Modal analysis of the fixture was performed based on the 3D finite element model,thus its natural frequencies and vibration modes were obtained to optimize the design. The natural frequencies、energy magnifying factor、scope of orthogonal motion and differences in vibration response among fixed points of the optimized fixture were analyzed to make sure the design meet the fixture design standardization. The result is verified through the vibration test and shows good performance of the fixture in vibration test.